Designing an AI-Integrated LMS: EFL Teachers’ Views on Affordances and Challenges - Yawan, Hendri; Abin, Rais; Marhamah; Maharani, Puan (Universitas Islam Ahmad Dahlan (UIAD), 2025)
The integration of generative artificial intelligence (GenAI) into English as a Foreign Language (EFL) learning is an emerging area of inquiry, particularly in contexts undergoing curriculum reform. This study explores how embedding ChatGPT into a Learning Management System (LMS) can support secondary EFL teachers’ instructional practices. Despite national efforts to improve digital infrastructure and pedagogical innovation, many EFL teachers still struggle with effectively using LMS platforms for language instruction. The study adopted a Design-Based Research (DBR) guided by the Software Development Life Cycle (SDLC) Waterfall model, to design, implement, and evaluate an AI-integrated LMS. Data were collected through surveys, interviews, and user walkthroughs with six secondary EFL teachers. Findings show that the AI-enhanced LMS improved usability, instructional planning, language material development, and teacher confidence. Teachers described the AI chatbot as a supportive thinking partner for generating lesson ideas, workload and encouraged pedagogical reflection. At the same time, they raised concerns about student overreliance, content accuracy, and the ethical boundaries of AI use. These insights highlight the importance of co-design, context-sensitive implementation, and critical digital literacy in GenAI integration. This study contributes to growing conversations on AI in secondary education by emphasizing the role of teacher agency, ethical awareness, and system adaptability. It suggests that GenAI, when grounded in local practice, can act not only as a technical tool but as a catalyst for language pedagogical instruction.